Nurse -Family Partnership (NFP): The Pursuit of Self-Sustainability - Wilson, Jonela; Avril Edwards Nichols; Khary Delves; Simon Bowen; Mena Salib (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
One in every seven children in the United States is born into poverty. These babies are at a higher risk of physical defects which can inevitably plunge them into the cycle of poverty. Nurse -Family partnership is a program that follows a theory- driven model that creates an avenue through which low-income, first time mothers are assisted by a home visiting nurse. Among NFP participants there is a reduction in infant mortality, abuse, neglect and crime; and an increase in the empowerment of young women. As of 2017, the program is challenged by funding issues due to heavy reliance on federal and philanthropic funding. This case explores the program’s options for self-sustainability in the long term.